2022
DOI: 10.3389/fnbeh.2022.846076
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Signature of Visual Learning Under Restrictive Virtual-Reality Conditions

Abstract: Honey bees are reputed for their remarkable visual learning and navigation capabilities. These capacities can be studied in virtual reality (VR) environments, which allow studying performances of tethered animals in stationary flight or walk under full control of the sensory environment. Here, we used a 2D VR setup in which a tethered bee walking stationary under restrictive closed-loop conditions learned to discriminate vertical rectangles differing in color and reinforcing outcome. Closed-loop conditions res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…, 2021; Lafon et al. , 2022). Fixation time (s) was defined as the time spent by each cylinder at the center of the screen (± 2.5 mm) where it was brought by the bee's actions (Lafon et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021; Lafon et al. , 2022). Fixation time (s) was defined as the time spent by each cylinder at the center of the screen (± 2.5 mm) where it was brought by the bee's actions (Lafon et al.…”
Section: Methodsmentioning
confidence: 99%
“…, 2022; Lafon et al. , 2022), among others. The full control offered by VR allows referring neural and molecular events recorded under these circumstances to the specific problem being solved by the insects.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, a series of behavioral studies of honeybees involving two-or three-dimensional VR conditions have reported that walking bees on a treadmill ball could learn to associate a visual stimulus with the location of the sucrose reward, similar to the free-ying bees in the Y-maze (Buatois et al 2017(Buatois et al , 2018Lafon et al 2021Lafon et al , 2022Geng et al 2022). In addition, the involvement of the mushroom body of the brain in visual learning under VR conditions has been suggested by electrophysiological recordings from mushroom body extrinsic neurons (Paffhausen et al 2020) and analyses of immediate early gene expression (Lafon et al 2022;Geng et al 2022). However, in all these previous studies, the bees did not y but walked on the treadmill ball, even though the honeybees y foraging.…”
Section: Introductionmentioning
confidence: 99%
“…This experimental setup allows us to present a stimulus more precisely than a free-ying condition and to easily investigate neural correlates of the learning behavior as the animal is tethered and moves stationary in the setup. Recently, a series of behavioral studies of honeybees involving two-or three-dimensional VR conditions have reported that walking bees on a treadmill ball could learn to associate a visual stimulus with the location of the sucrose reward, similar to the free-ying bees in the Y-maze (Buatois et al 2017(Buatois et al , 2018Lafon et al 2021Lafon et al , 2022Geng et al 2022). In addition, the involvement of the mushroom body of the brain in visual learning under VR conditions has been suggested by electrophysiological recordings from mushroom body extrinsic neurons (Paffhausen et al 2020) and analyses of immediate early gene expression (Lafon et al 2022;Geng et al 2022).…”
Section: Introductionmentioning
confidence: 99%